2011
DOI: 10.1149/1.3571529
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mechanical Planarization Mechanism for Nitrogen-Doped Polycrystalline Ge2Sb2Te5 Film Using Nitric Acidic Slurry Added with Hydrogen Peroxide

Abstract: We investigated the chemical mechanical planarization (CMP) mechanism of nitrogen-doped polycrystalline Ge 2 Sb 2 Te 5 (pc-GST) using nitric acid slurry without or with 1.0 wt % hydrogen peroxide (H 2 O 2 ). Without H 2 O 2 , the pc-GST film surface undergoes selective corrosion of Ge and Sb, resulting in pitting corrosion. Otherwise, with H 2 O 2 , the pc-GST film surface produces a Ge, Sb, Te oxide layer, thereby introducing a cyclic polishing process such as chemical oxidation, chemical and mechanical polis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The decrease in polishing rate with increase of H 2 O 2 concentration beyond 0.5 wt% was believed to be due to the stronger passivation of the TST surface. 8 This effect could be contributed to the formation of oxide in peroxide solutions or the adsorption of OH radicals on the TST surface. 9 In the future study, we will be proposing a possible mechanism of the TST film polishing rate with various H 2 O 2 concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The decrease in polishing rate with increase of H 2 O 2 concentration beyond 0.5 wt% was believed to be due to the stronger passivation of the TST surface. 8 This effect could be contributed to the formation of oxide in peroxide solutions or the adsorption of OH radicals on the TST surface. 9 In the future study, we will be proposing a possible mechanism of the TST film polishing rate with various H 2 O 2 concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the component of the chemical oxide layer on the a-GST surface, Zhong et al [13] reported that it was GeO 2 , Sb 2 O 5 , and TeO 2 formed in the a-GST film surface in the acidic condition with 2.0 wt% H 2 O 2 . In our study, according to Pourbaix diagrams in a water system in the standard condition [14] for Ge, Sb, and Te, the corrosion potential of a-GST (less than 0.02 V) below 0.5 wt% H 2 O 2 is located in the domain of GeO 2 , Sb/Sb oxide boundary, and Te. In contrast, for above 0.…”
Section: Resultsmentioning
confidence: 77%
“…Their results show that GeO 2 , Sb 2 O 5 , and TeO 2 were formed on the a-GST surface after a-GST was dipped in the slurry for 10 min, but no detailed discussion about the removal mechanism was given. Cui et al [14] investigated CMP of N-GST using nitric acidic slurry with 1.0 wt% H 2 O 2 and found the addition of H 2 O 2 could suppress selective pits corrosion of N-GST, and removal of N-GST followed a cyclic polishing mechanism with 1.0 wt% H 2 O 2 . However, few studies were reported on other concentrations of H 2 O 2 such as that below 1.0 wt% in the acidic slurry.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed peak identification and its binding energy were referred to from some previously reported results. [18][19][20] For the pc-GST film dipped in the H 2 O 2 containing solution without CA, GeO 2 , Sb 2 O 5 , and TeO 2 peaks were found due to the oxidizing power of H 2 O 2 in a slurry. As the CA concentration increased to 0.1 wt%, the TeO 2 peak decreased and Te-metal (homopolar bonds of Te, Te-Sb, or Te-Ge) peaks increased.…”
Section: Resultsmentioning
confidence: 99%